KINETICS AND MECHANISMS OF TRITIUM RELEASE FROM LITHIUM TITANATE DURING REACTOR IRRADIATION - Beckman, I.N.; Tazhibayeva, I.L.; Kuykabaeva, A.A. (Recent Contributions to Physics, 2008)
Goal of this work is to study kinetics and mechanisms of tritium generation and release from lithium titanate during long-term irradiation. Paper contains results of the study of kinetics of tritium release from irradiated lithium ceramic samples depending on irradiation conditions under constant temperature and thermal cycling. The mechanisms are proposed for tritium generation and release from lithium ceramics during long-term reactor irradiation. It was showed that lithium metatitanate-based ceramics, which is high-enriched with lithum-6, can be steady (at least up to burnup level of 22%) tritium source for fusion facilities.